2000
DOI: 10.1089/088922200309115
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Can Infect Human Retinal Pigment Epithelial Cells in Culture and Alter the Ability of the Cells to Phagocytose Rod Outer Segment Membranes

Abstract: Human immunodeficiency virus type 1 (HIV-1) has been found in the vitreous of persons with AIDS. Here we investigated the susceptibility of human retinal pigment epithelial (RPE) cells to HIV-1 infection in culture and the effects of HIV-1 on the phagocytic function of the RPE. We found that 10 of 11 populations of RPE cells isolated from different fetal or adult eyes were susceptible to low-level replication of HIV-1/NL4-3 as determined by the detection of viral DNA and spliced viral RNA encoding envelope. HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 68 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…This process of general fusion between two membranes (in this case, between the exosomal and target cell membranes) is thought to occur in most cell types as a method of information exchange between cells that does not require direct intercellular contact. It has been shown that HIV is able to infect a broad spectrum of cell types, including cells that lack viral receptors such as fibroblasts (48,49), hepatocytes (50), and epithelial cells (51,52). These observations strongly support the Trojan exosome model, which predicts that many cell types will be infected at low efficiency by the uptake of HIV through the existing pathway for exosomal exchange.…”
Section: Half-maximal Signal Titers In Exosomes For Five Proteins Of mentioning
confidence: 76%
“…This process of general fusion between two membranes (in this case, between the exosomal and target cell membranes) is thought to occur in most cell types as a method of information exchange between cells that does not require direct intercellular contact. It has been shown that HIV is able to infect a broad spectrum of cell types, including cells that lack viral receptors such as fibroblasts (48,49), hepatocytes (50), and epithelial cells (51,52). These observations strongly support the Trojan exosome model, which predicts that many cell types will be infected at low efficiency by the uptake of HIV through the existing pathway for exosomal exchange.…”
Section: Half-maximal Signal Titers In Exosomes For Five Proteins Of mentioning
confidence: 76%
“…It has been hypothesized that they may be partially responsible for loss of visual function and visual field [16-18]. A limited number of human studies have been performed with animal models providing the bulk of our knowledge on retinal gene expression to date.…”
Section: Introductionmentioning
confidence: 99%
“…The RPE can ingest a variety of different particles including possible pathogens, as has been shown for yeast and molds [5,6]. Also, viral agents can have a profound effect on the phagocytic capacity of the RPE, as has recently been shown for HIV [7]. This is of special interest for the data previously presented by our group, namely that several human viruses of different virus classes are able to infect human retinal pigment cells [8] and can induce changes in surface receptor expression of immune-regulatory molecules on RPE cells [9].…”
Section: Introductionmentioning
confidence: 91%